Orofacial cysticercosis – A retrospective clinicopathological and imaging study of 16 cases. Issue 6 (November 2016) - Gupta, Ambika; Singh, Cheena; Singh, Harneet; Narwal, Anjali; Singh, Virendra
Abstract: Objective: The purpose of the study was to evaluate the clinical, imaging and histopathological features of orofacial cysticercosis. Materials and method: This study is a retrospective analysis of orofacial cysticercosis that was diagnosed in the Department of Oral Medicine and Radiology, PGIDS, Rohtak during the period from January 2012 to December 2014. A total of 16 cases were analyzed for their clinical, imaging, histological features and management. Result: From all the 16 evaluated patients 68.75% were females and 31.25% males. Age ranged from 10 years to 55 years with a mean of 25.69 years. In all the patients, the chief complaint was a nodular swelling of variable duration with a wide variation in the location. Most of the cases were diagnosed on ultrasonography alone except for one case that needed MRI. All the patients were managed medically with only five out of 16 patients requiring surgical intervention. Conclusion: Cysticercosis should be included in the differential diagnosis of all the nodular swellings of head and neck region. Ultrasound is an economic, easily accessible, safe and noninvasive method that can be used with a considerable reliability in the diagnosis of cysticercosis along with histopathological examination. Clinical relevance: Cysticercosis is a rare disease difficult to diagnose clinically due to nonspecific presentation and inconclusive investigations. This study, to the best of our knowledge, is the first compilation of 16 cases of orofacial cysticercosis. Dentist may play a key role in diagnosis, which may have more widespread implications.